How does Realistic Mathematics Learning Shape Learners' Problem Solving and Critical Thinking Skills? - Amir, Fadila; Firdaus, ⁠Fery Muhamad; Pada, Amir (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education is vital for fostering problem-solving and critical thinking skills in students, essential for thriving in a globalized world. This study investigates the impact of the Realistic Mathematics Education (RME) approach on enhancing these skills among primary school students. Utilizing a quasi-experimental design with a pretest-posttest control group, the research involved 44 second-grade students, split evenly between classes II A and II B. Data analysis was conducted using descriptive and statistical techniques, employing SPSS 25.0 for Windows to evaluate the effects of the RME approach. The significance value for both problem-solving and critical thinking abilities was 0.000, indicating a substantial impact of the RME approach on these skills. The findings suggest that integrating realistic learning with other methodologies, such as project-based learning or developing media based on realistic principles, could further enhance educational outcomes.